Community Literacy Ecosystem to Enhance Elementary Students’ Reading Comprehension - Mahmudah, Mahmudah; Tri Mulyono; Khusnul Khotimah (Jurnal Elementaria Edukasia, 2025)
This study explores the contribution of a community-based literacy ecosystem to improving elementary students’ reading comprehension skills. The research was inspired by the continuing decline in national literacy scores and the limited participation of parents and local communities in supporting children’s reading development. School-based literacy activities are often routine and lack integration with home and community engagement. A quantitative approach with a causal-comparative design was employed. The participants were third- and fifth-grade students of SD Negeri Jejeg 01, Bumijawa District, Tegal Regency. Data were gathered using reading comprehension tests and parental support questionnaires. The data were analyzed using difference tests and moderated regression models to determine the moderating effect of parental involvement on the relationship between community literacy programs and reading comprehension. The findings reveal that participation in community literacy initiatives significantly enhances students’ understanding of reading materials. Furthermore, parental support strengthens the influence of community participation on children’s reading comprehension performance. This study underscores the importance of establishing collaboration among schools, families, and local communities to build a sustainable and meaningful literacy culture for young learners.